Sleep Disorders' Prevalence in People with Headache: A Cross-Sectional Study in Urban Population (2011)
Documento de conferencia Sleep Disorders' Prevalence in People with Headache: A Cross-Sectional Study in Urban Population. Elaborado por Yuri Takeuchi Tan, M Rueda-Sanchez, F Silva, J Muñoz, B Uribe Garcia, F Sobrino, S Ramírez, J Calderon Gónzalez, publicada en la revista Headache